2019
DOI: 10.1017/etds.2019.41
|View full text |Cite
|
Sign up to set email alerts
|

The sets of Dirichlet non-improvable numbers versus well-approximable numbers

Abstract: Let Ψ : [1, ∞) → R + be a non-decreasing function, a n

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…It can readily be seen that the divergence case of Jarnik's theorem played a pivotal role in proving the divergence case of the Theorem 1.5. Further, it is worth pointing out that the difference set G(Ψ) \ K(3Ψ) is non-trivial as the Hausdorff dimension of this set is the same as that of G(ψ) as proved in [1]. We refer the reader to [7] for the Lebesgue measure and Hausdorff dimension results for a generalised form of the set G(Ψ).…”
Section: Continued Fractions and Dirichlet Improvabilitymentioning
confidence: 90%
“…It can readily be seen that the divergence case of Jarnik's theorem played a pivotal role in proving the divergence case of the Theorem 1.5. Further, it is worth pointing out that the difference set G(Ψ) \ K(3Ψ) is non-trivial as the Hausdorff dimension of this set is the same as that of G(ψ) as proved in [1]. We refer the reader to [7] for the Lebesgue measure and Hausdorff dimension results for a generalised form of the set G(Ψ).…”
Section: Continued Fractions and Dirichlet Improvabilitymentioning
confidence: 90%
“…This is in turn related to the Dirichlet improvable sets discussed in [1,8,9]. This will be the subject of a forthcoming article.…”
Section: Introductionmentioning
confidence: 87%
“…They showed that if lim n→∞ ϕ(n) = ∞ and lim n→∞ ϕ(n)/ϕ(n + ϕ(n)) = 1, then the set E ϕ α,β is of full Hausdorff dimension for all α, β with 0 ≤ α ≤ β ≤ ∞. Tong et al [19] generalised these results to the βexpansion x = ∞ k=1 x n /β n for β ∈ (1,2]. (For more information on the β-expansion, see [2,6,22].…”
Section: Introductionmentioning
confidence: 99%
“…The result of Barral and Seuret was further generalized to the setting of continued fractions by Wang et al in [21]. To refer to their result, we first restate the Jarník-Besicovitch set (1)(2)(3)(4) in terms of growth rate of partial quotients, J(τ) = {x ∈ [0, 1) : a n (x) ≥ e ((τ−2)/2)S n (log |T (x)|) for i.m. n ∈ N}.…”
Section: Introductionmentioning
confidence: 99%
“…dim H {x ∈ [0, 1) : a n+1 (x) ≥ e τ(x)S n h(x) for i.m. n ∈ N} = s (1) N . • When r = 1, τ(x) = 1 and h(x) = log B, we obtain the result by Wang and Wu [20].…”
Section: Introductionmentioning
confidence: 99%